2005
DOI: 10.1007/s00037-005-0199-5
|View full text |Cite
|
Sign up to set email alerts
|

Language compression and pseudorandom generators

Abstract: Abstract. The language compression problem asks for succinct descriptions of the strings in a language A such that the strings can be efficiently recovered from their description when given a membership oracle for A. We study randomized and nondeterministic decompression schemes and investigate how close we can get to the information theoretic lower bound of log A =n for the description length of strings of length n. Using nondeterminism alone, we can achieve the information theoretic lower bound up to an addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This leads to the general idea of considering time-bounded versions of Kolmogorov complexity. An interesting line of research [Sip83,BFL01,BLvM05,LR05] in time-bounded Kolmogorov complexity, which we also pursue in this paper, focuses on a notion called time-bounded distinguishing Kolmogorov complexity, CD t (·), introduced by Sipser [Sip83]. We say that a description (called a program in the Kolmogorov complexity literature) p distinguishes a string x if p accepts x and only x. CD t,A (x) is the size of the smallest program that distinguishes x and that runs in time t(|x|) with access to the oracle A. Sipser showed that, for every set B and every length n, there is a string w of length poly(n) such that, for every x ∈ B =n , CD poly,B =n (x | w) ≤ log(|B =n |)+log log(|B =n |)+O(1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to the general idea of considering time-bounded versions of Kolmogorov complexity. An interesting line of research [Sip83,BFL01,BLvM05,LR05] in time-bounded Kolmogorov complexity, which we also pursue in this paper, focuses on a notion called time-bounded distinguishing Kolmogorov complexity, CD t (·), introduced by Sipser [Sip83]. We say that a description (called a program in the Kolmogorov complexity literature) p distinguishes a string x if p accepts x and only x. CD t,A (x) is the size of the smallest program that distinguishes x and that runs in time t(|x|) with access to the oracle A. Sipser showed that, for every set B and every length n, there is a string w of length poly(n) such that, for every x ∈ B =n , CD poly,B =n (x | w) ≤ log(|B =n |)+log log(|B =n |)+O(1).…”
Section: Introductionmentioning
confidence: 99%
“…The precision term poly log(n · 1/ε) has been improved to O(log(n · 1/ε)) in [BMVZ13]. In addition, Buhrman, Lee, and van Melkebeek [BLvM05] showed that for all B and x ∈ B =n , CND poly,B =n (x) ≤ log(|B =n |) + O(( log(|B =n |) + log n) log n), where CND is similar to CD except that the distinguisher program is nondeterministic.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the idea of considering a time-bounded version of Kolmogorov complexity. An interesting line of research [Sip83,BFL01,BLvM05,LR05], which we also pursue in this paper, focuses on the time-bounded distinguishing Kolmogorov complexity, CD t (·). We say that a program p distinguishes x if p accepts x and only x. CD t,A (x) is the size of the smallest program that distinguishes x and that runs in time t(|x|) with access to the oracle A. Buhrman, Fortnow, and Laplante [BFL01] show that for some polynomial p, for every set B, and every string x ∈ B =n , CD p,B =n (x) ≤ 2 log(|B =n |) + O(log n).…”
Section: Introductionmentioning
confidence: 99%
“…Buhrman, Fortnow, and Laplante [BFL01] show that log(|B =n |) can be achieved if we allow a few exceptions: For any B, any ǫ, for all except a fraction of ǫ strings x ∈ B =n , CD poly,B =n (x) ≤ log(|B =n |) + poly log(n · 1/ǫ). Buhrman, Lee, and van Melkebeek [BLvM05] show that for all B and x ∈ B =n , CND poly,B =n (x) ≤ log(|B =n |) + O(( log(|B =n |) + log n) log n), wher CND is similar to CD except that the distinguisher program is nondeterministic.…”
Section: Introductionmentioning
confidence: 99%
“…The study of language compression (see e.g. Buhrman et al 2004 for recent results and references to earlier work) focuses on the worst-case compressibility (in the above sense) for sources that are flat over an efficiently decidable support (i.e. sources with membership oracles, just as we study).…”
Section: Introductionmentioning
confidence: 99%